Enteroenteric fistulae after ingestion of multiple magnets in children - Gamal Al-Saied; Omar Alsamahy; Medhat Ibrahim; Talal Al-Malki; Riadh BenMalek; Rachid Khemakhem; Ziyad AlNefaie; Tharwat Hussain; Yasmine Shafik; Riyad Thabet; Gulfam Farhan; Ahmed Gamal; et al. (Elsevier, 2022)
Background: Infants and young children explore objects by putting them in the mouth. Although most swallowed foreign bodies pass spontaneously through the gastrointestinal tract without causing harm, some of them are potentially dangerous and may be lethal. Patients and methods: Five children (3boys and 2girls) have swallowed multiple high strength and powerful rare earth element Neodymium magnets. Their ages ranged between (nine months to six-year-old). Three cases were subjected to open and two for laparoscopic exploration (one of them converted to open). Results: multiple complicated enteroenteric fistulae in three cases and multiple perforation of small intestine in two cases. Resection anastomosis was done for one case and simple closure of small bowel perforations for other four cases. Post operative course was uneventful for all patients and discharged in a good general condition. Conclusion: General practitioners should be aware of the danger and complications of Neodymium magnetic beads ingestion by children. Early endoscopic removal is recommended if the patient presents immediately after ingestion. Parents awareness through media is required to abandon magnet balls in houses and where children can ingest those dangerous balls.